Epizod szczeciński w prozie Bohumila Hrabala. Rzecz o granicach tłumaczenia / The Szczecin Episode in Bohumil Hrabal’s Prose On the Limits of Translation - Soliński, Wojciech (Przekłady Literatur Słowiańskich, 2019)
The object of the analysis is the so-called Szczecin episode in its many variants. The episode plays a significant role in interpreting the novel Too Loud a Solitude, the Czech version of which is a source text for a number of foreign translations. As such, the episode creates space for specific translation operations that are possible in some languages (e.g. Polish and German), while impossible in other.